Endoscopic lumbar foraminotomy for foraminal stenosis in stable spondylolisthesis - Ahn, Yong; Park, Han Byeol; Yoo, Byung Rhae; Jeong, Tae Seok (Frontiers in Surgery, 2022)
Background: Open decompression with fusion is the gold-standard surgical technique for spondylolisthesis. However, it may be too extensive for patients with foraminal stenosis with stable spondylolisthesis. The endoscopic lumbar foraminotomy (ELF) technique was developed as a minimally invasive surgical option for foraminal stenosis. Some authors have reported the outcomes of ELF for various spondylolistheses. However, few studies have demonstrated foraminal stenosis in advanced stable spondylolisthesis. This study aimed to describe the surgical technique and results of ELF for radiculopathy due to foraminal stenosis in patients with stable spondylolisthesis. Methods: Consecutive 22 patients who suffered from radiculopathy with spondylolisthesis underwent ELF. The inclusion criterion was unilateral radicular leg pain due to foraminal stenosis in stable spondylolisthesis. After the percutaneous transforaminal approach, foraminal decompression was performed using various surgical devices under endoscopic visualization. Surgical outcomes were measured using the visual analog pain score, Oswestry disability index, and modified MacNab criteria. Results: Pain scores and functional outcomes improved significantly during the 12-month follow-up periods. The rate of clinical improvement was 95.5% (21 of 22 patients). One patient experienced a dural tear and subsequent open surgery. Conclusion: ELF can be effective in foraminal stenosis in stable spondylolisthesis. Technical points specializing in foraminal decompression in spondylolisthesis are required for clinical success.